Exploring the Role of Machine Translation in Vocabulary Acquisition: A Case Study on EFL Learners Using the Reverso Context Application - Merghoub, Chahra; Mhamedi ,Nadir (Faculty of Letters and Foreign Languages Department of English, 2025)
Machine translation has remarkably become an important tool for vocabulary learning in modern education. Therefore, this research aimed to investigate the effectiveness of Reverso context application on vocabulary development. The research employed a quazi experimental design consisting of a pre-task and post-task comparison to assess the impact of reverso context application on vocabulary development. Furthermore, a qualitative focus group discussion was carried out to explore students’ experiences and perceptions toward the use of Reverso. The results revealed that Reverso application contributed in the improvement of students’ translation of vocabularies and sentence construction. Additionally, the students expressed their interest using the application, they appreciated its features namely ease of use and rapidity, besides the contextual examples. However, some of them expressed their concerns about some issues such as confusion and excessive reliance on this tool that potentially could lead to unnecessarily complicated language. Ultimately, this research highlights the role of machine translation tools for vocabulary learning and emphasizes the effective integration of such tools in educational setting.